Rural-Urban Interaction in the Developing World - Lynch, Kenny (Routledge Perspectives on Development, 2005)
Sustaining the rural and urban populations of the developing world has been identified as a key global challenge for the twenty-first century. Rural-Urban Interaction in the Developing World is an introduction to the relationships between rural and urban places in the developing world and shows that not all their aspects are as obvious as migration from country to city. There is now a growing realization that rural-urban relations are far more complex. Using a wealth of student-friendly features including boxed case studies, discussion questions and annotated guides to further reading, this innovative book places rural-urban interactions within a broader context, thus promoting a clearer understanding of the opportunities, as well as the challenges, that rural-urban interactions represent.